Kesiapan Public Space di Kota Pontianak Menghadapi Kondisi New Normal Pasca Covid 19 - Chandra Bayu; Fery Kurniadi (Universitas Sebelas Maret Surakarta, 2021)
Covid 19 pandemic that strike the world, has had a major impact on changes people's lives. The changes as a result of the application of social distancing, which is done to slow and stop the spread of disease, termed ‘New Normal’. This study aims to determine changes in socio-spatial conditions on the use and to determine the readiness of public spaces in Pontianak in accommodating the new normal. In addition, the results of this study will contribute ideas related to the development of learning in designing public spaces in the future. Mix Method approach has been used. Importance and performance analysis have been used to analyze the quantitative datas and the qualitative data has been observed by place centered mapping. By comparing the quantitative and qualitative output, the result show the public space readiness indicator are: all public spaces with good performance in accommodating recreational and social activities; two public space with good performance in accommodating sport activities; The need to improved ‘health protocols’ control and WASH; recessive' mechanism in apply physical distancing; inconsistency of Expectation – Behavior; and unimportance of the tele-working / tele-learning.